Efficiency assessment of balancing devices application in the lighting systems of buildings - Романова, Тетяна Іванівна (Technology audit and production reserves, 2014)
In the article there are discussed the using of balancing devices in lighting systems of buildings carried out on the basis of lighting devices with LED light sources, in order to increase their efficiency by eliminating the single-ended modes, which arise at random switching on and switching off the power single-phase receivers and lighting loads. It is proposed the possible variants for power supply of lighting devices with LED light sources, including through the balancing thyristor voltage regulator, which is a source of direct current and fully balanced the load. Transition to the DC power supply will help reduce losses, costs of electricity and the higher harmonic components of current and voltage, increase the coefficients of power, reliability and electrical safety of these systems. The technical and economic evaluation of different variants of power supply of LED light sources is done in the article, the variant with the best specifications is proposed. It is proposed in the future to perform the scheme of power supply of buildings in combined variant, which implies the power supply of power electrical receivers from AC 380/220 V, and the lighting power consumers - from the DC network.